THE INFLUENCE OF THINK TALK WRITE STRATEGY TO THE STUDENTS` ABILITY IN WRITING - Insenalia Sampe Roli Hutagalung (LPPM Universitas Darma Agung, 2021)
This research aims to get the effect of using Think Talk Write Strategy on students’ writing descriptive text. This research is quantitative research that applies Quasi-Experimental design. The researcher took 10 students of Germany Study Program of Teacher Training Faculty of Universitas HKBP Nommensen Pematangsiantar as the participants of the research by using purposive sampling.The data was gained through essay test. The students’ writing was scored by using Brown’s Formula. To analyze the data, the researcher used IBMSPSS 20.0. From data analysis, mean of the writing score in experimental group is 81.58, meanwhile mean of the writing score in control group is 64.20. The result of analyzing the data shows the score of t-test is higher than t-table (5.12> 1.67). It can be concluded that there is a significant influence of usingThink Talk Write teaching strategy to the students` ability in writing a descriptive text